2012
DOI: 10.1063/1.4746990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photo detectors and operating conditions for decay time determination in phosphor thermometry

Abstract: M. (2012). Comparison of photo detectors and operating conditions for decay time determination in phosphor thermometry. Review of Scientific Instruments, 83(9), [094901]. DOI: 10.1063/1.4746990 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…This Raman scattering (along with any prompt fluorescence) does not persist beyond the short laser excitation pulse (typically about 10 ns duration) and therefore precedes most of the phosphor sensor decay curve. However, this high signal intensity spike distorts the ensuing decay as either one or both of the detector (such as a photomultiplier tube) and electronic measurement instrument (such as an oscilloscope) recover from the spike [26][27][28]. With no filtering in a single fiber probe configuration to remove the background light intensity generated in the laser delivery fiber and probe, the initial spike can significantly distort the measured phosphor emission decay for several microseconds.…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…This Raman scattering (along with any prompt fluorescence) does not persist beyond the short laser excitation pulse (typically about 10 ns duration) and therefore precedes most of the phosphor sensor decay curve. However, this high signal intensity spike distorts the ensuing decay as either one or both of the detector (such as a photomultiplier tube) and electronic measurement instrument (such as an oscilloscope) recover from the spike [26][27][28]. With no filtering in a single fiber probe configuration to remove the background light intensity generated in the laser delivery fiber and probe, the initial spike can significantly distort the measured phosphor emission decay for several microseconds.…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…A Hamamatsu H11526-20-NF photomultiplier tube was used as the detector. According to recent investigations by the authors, this PMT type showed superior signal linearity compared to other detector types [13]. A control voltage of 0.339 V set the photomultiplier gain constant throughout the entire experiment.…”
Section: Methodsmentioning
confidence: 99%
“…A well-constructed calibration curve is important for an accurate thermographic phosphor temperature determination. The process of obtaining a phosphor calibration curve can be tedious and accompanied with effects such as detector nonlinearity [13,14]. Despite the importance of the calibration, no major development has occurred or been reported for the method by which the temperature calibration is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Severe signal distortions can occur to the measured signal if the detector is operating in its nonlinear region. The importance of detector linearity in phosphor thermometry was characterized and reported by Knappe et al [25,26]. The studies showed that photodetectors can severely distort the shape of the exponentially decaying signals.…”
Section: Detector Linearitymentioning
confidence: 99%
“…By testing an array of different photodetectors, the authors have identified a detector that provides superior linearity response among the tested photodetectors [26]. This detector is the Hamamatsu H11526-20-NF.…”
Section: Detector Linearitymentioning
confidence: 99%